Ukraine - СERN: the Way to Cooperation - Grinyov, B.V.; Titov, M.P.; Stadnik, P.O. (Science and Innovation, 2024)
Introduction. The European Organization for Nuclear Research (СERN) is the world largest laboratory for high-energy physics and a platform for creative relationship between researchers from different countries. Problem Statement. The development of international scientific cooperation, in particular, the creation of conditions for expanding the participation of Ukrainian researchers in carrying out the largest physical experiments on nuclear physics, gaining new knowledge and facilitating the innovation processes in Ukraine. Purpose. To analyze factors that facilitate the development of cooperation between Ukrainian researchers and CERN and to outline prospects for the future. Materials and Methods. Analysis of CERN research activities in the context of international cooperation and outlook of CERN international research projects in high-energy physics. Results. The way of cooperation with Ukraine from the very beginning of the CERN creation to the signature of the Agreement on Associate Membership of Ukraine in CERN has been analyzed. Examples of the positive impact of cooperation with CERN on innovation processes in Ukraine, in particular, in the field of the development and production of new hightech materials, which are crucially important for implementing state-of-the-art experiments in high-energy physics have been considered. The associate membership has allowed Ukrainian researchers to participate more actively in the study of the global physical phenomena of the universe in the most advanced experimental laboratory and engineers and technicians to master the cutting-edge innovative technologies, including informational and medical ones. Prospects of the further cooperation have been outlined. Conclusions. Cooperation with CERN enables Ukraine to take advantage of CERN mission, one of the main tasks of which is the cohesion of people from different countries and cultures through science. Teachers, students, and schoolchildren of Ukraine have got new opportunities to work with the state-of-the-art methods, modern equipment, and innovative approaches in the training of highly qualified specialists in physics and related fields of science and technology.